Novel Cellular Functions of Very Long Chain-Fatty Acids: Insight From ELOVL4 Mutations - Deák, Ferenc; Anderson, Robert E.; Fessler, Jennifer L.; Sherry, David M. (Frontiers in Cellular Neuroscience, 2019)
Elongation of Very Long chain fatty acids-4 (ELOVL4) protein is a member of the ELOVL family of fatty acid elongases that is collectively responsible for catalyzing formation of long chain fatty acids. ELOVL4 is the only family member that catalyzes production of Very Long Chain Saturated Fatty Acids (VLC-SFA) and Very Long Chain Polyunsaturated Fatty Acids (VLC-PUFA) with chain lengths ≥ 28 carbons. ELOVL4 and its VLC-SFA and VLC-PUFA products are emerging as important regulators of synaptic signaling and neuronal survival in the central nervous system. Distinct sets of mutations in ELOVL4 cause three different neurological diseases in humans. Heterozygous inheritance of one set of autosomal dominant ELOVL4 mutations that leads to truncation of the ELOVL4 protein causes Stargardt-like macular dystrophy (STGD3), an aggressive juvenile-onset retinal degeneration. Heterozygous inheritance of a different set of autosomal dominant ELOVL4 mutations that leads to a full-length protein with single amino acid substitutions causes spinocerebellar ataxia 34 (SCA34), a late-onset neurodegenerative disease characterized by gait ataxia and cerebellar atrophy. Homozygous inheritance of a different set of ELOVL4 mutations causes a more severe disease with infantile onset characterized by seizures, spasticity, intellectual disability, ichthyosis, and premature death. ELOVL4 is expressed widely in the CNS and is found primarily in neurons. ELOVL4 is expressed in cell-specific patterns within different regions of the CNS that are likely to be related to disease symptoms. In the retina, ELOVL4 is expressed exclusively in photoreceptors and produces VLC-PUFA products that are incorporated into phosphatidylcholine and enriched in the light sensitive membrane disks of the photoreceptor outer segments. VLC-PUFA are enzymatically converted into “elovanoid” compounds that appear to provide paracrine signals that promote photoreceptor and neuronal survival. In the brain, the main ELOVL4 products are VLC-SFA that are incorporated into sphingolipids and enriched in synaptic vesicles, where they regulate kinetics of presynaptic neurotransmitter release. Understanding the function of ELOVL4 and its VLC-SFA and VLC-PUFA products will advance our understanding of basic mechanisms in neural signaling and has potential for developing novel therapies for seizure and neurodegenerative diseases, including ataxias and blindness.